About Spanish Catholicism in the 21st Century: From official religion to a cultural complement? - Pereira Menaut, Antonio-Carlos (Mercurio Peruano, 2016)
Anyone who asks about the background of the current Spanish political and economic crisis will first detect a number of political causes in the same electoral system that favors the government of political parties with insufficient separation of powers; without forgetting the role of the European Union. But if someone deepens, possibly he or she ends discovering an anthropological change, where the institutional and legal changes are important, but smaller. For this purpose the performance of the Spanish Episcopal Conference regarding the fundamental role of the Catholic religion in Spanish society is analyzed. This essay has not been written from the theology field, but from a legal vision of a constitutionalist who tries to understand what is happening today in Spain, mostly in order to step back and apply common sense.